Occurrence of Paratanaisia spp. Freitas, 1951 in a domiciled cockatiel (Nymphicus hollandicus, Psittaciformes: Cacatuidae) - Santi, Mariele De; Couto, Caroline Do; Werther, Karin (Colégio Brasileiro de Parasitologia Veterinária, 2018)
AbstractDigenetic eucotylids of the Paratanaisia genus are widely reported parasites of the avian renal system. The infection, commonly reported in free-living and zoo-housed birds, is described for the first time in a domiciled bird, a cockatiel kept as pet bird with free access to the yard outdoors. The bird was received at Veterinary Hospital, where clinical and radiographic evaluations suggested a case of heavy-metal poisoning. Although the bird received supportive care and a chelating agent, it died the next day. The necropsy showed friable kidneys and congestion of blood vessels in structures such as the skin, proventriculus, brain, and skullcap. The histopathological evaluation of the kidneys revealed multifocal hemorrhages, commonly found in cases of heavy-metal poisoning. Parasitic structures similar to those of the digenean trematodes Paratanaisia spp. were also observed inside dilated collecting ducts, which presented epithelial cell flattening and vacuolization. There was compression of adjacent tissue and discrete fibrotic areas. In the presence of intermediate hosts in the yard, the synanthropic nature of some wild free-living birds could make them a source of trematodes infection and dissemination for pet birds. Conversely, the infected cockatiel could also have served as a reservoir and carrier of trematodes to wild free-living birds.

ResumoEucotilídeos digenéticos do gênero Paratanaisia são amplamente descritos como parasitas do trato urinário de aves. A infecção, comumente relatada em aves de vida livre e em zoológicos, é descrita pela primeira vez em uma ave domiciliada, uma calopsita mantida como ave de companhia com livre acesso ao jardim externo. A ave foi recebida no Hospital Veterinário onde avaliações clínicas e radiográficas sugeriram um quadro de intoxicação por metal pesado. Embora tenha recebido tratamento de suporte e agente quelante a ave veio a óbito no dia seguinte. A necropsia demonstrou rins de consistência friável e congestão dos vasos sanguíneos da pele, proventrículo, cérebro e calota craniana. A avaliação histopatológica dos rins revelou hemorragias multifocais comumente observadas em intoxicação por metais pesados. Estruturas parasitárias similares àquelas observadas em Paratanaisia spp. foram observadas no interior de ductos coletores dilatados, os quais apresentavam achatamento e vacuolização de células epiteliais. Havia compressão do tecido adjacente e discretas áreas de fibrose. Na presença de hospedeiros intermediários no jardim, a condição sinantrópica de algumas aves de vida livre poderia torná-las fonte de infecção e disseminação de trematódeos para aves domiciliadas. Em contrapartida, a calopsita infectada poderia também servir como reservatório e carreador de trematódeos para aves de vida livre.
Ocorrência de Paratanaisia spp. Freitas, 1951 em calopsita (Nymphicus hollandicus, Psittaciformes: Cacatuidae) domiciliada
Keywords: Cockatiel; kidneys; histopathology; trematodes; Eucotylidae; Calopsita; rins; histopatologia; trematódeos; Eucotylidae